Molecular cloning, bioinformatics of the duck RIG-1 promoter region, and its differential expression profiles in embryo stages - LUO Jun; LIU Hehe; LIU Junying; ZHANG Tao; WANG Yushi; HAN Chunchun (浙江大学学报. 农业与生命科学版)
The retinoic acid inducible gene-1-like receptors (RLRs) play an important role in innate immune system. RIG-1, as a member of RLRs, belongs to intracellular protein and is closely related to cell proliferation, differentiation and innate antiviral immunity. It is widely accepted that the RIG-1 is absent in chicken genome, whereas exists in the duck’s, which may account for the stronger abilities of waterfowl than chicken in antivirus. Promoter, as the central element of gene expression regulation, can affect gene function by regulating mRNA transcription. However, there is still no report focusing on avian RIG-1 promoter. The purpose of this study was to investigate the characteristics of duck RIG-1 promoter region and its differential expression profiles in embryo stages.5' flanking promoter sequence of duck RIG-1 was obtained by PCR amplification and was analyzed by bioinformatics. The expression profiles of RIG-1 were detected by qRT-PCR in immune organs during duck embryonic development, as well as the predicted transcription factors regulating RIG-1 transcription.4 372 bp of duck RIG-1 promoter region was finally obtained. Bioinformatics analysis showed that typical elements, including TATA-box, CAAT-box, and binding sites of transcription factors, such as IRF-1, RXR, RAR, AP1, NF-κB, SP1, IL6 and Pax-2, were distributed in duck RIG-1 promoter region. Studies had demonstrated that IRF-1 can promote the expression of human RIG-1 and Pax-2 can inhibit the expression of mouse RIG-1. Besides, a CpG island with 65.8% GC content was predicted in duck RIG-1 promoter region, which has been found in mouse too. These data indicated that a similar transcription regulation manner may exist in duck with human and mouse. The results of qRT-PCR demonstrated that RIG-1 expression levels were dynamic in immune organs during duck embryo stages, and the expression of RIG-1 in bursa of Fabricius is higher than in spleen and thymus. Clustering of gene expression pattern showed that RIG-1 had similar expression patterns with IRF-1, RXR, AP1, NF-κB and IL6 in bursa of Fabricius, which may be due to that the bursa of Fabricius, compared with thymus and spleen, had relatively complete structure and function in duck embryo stages. This result indicated that they might regulate the transcription of RIG-1. Moreover, RIG-1 always had similar expression pattern with IRF-1 and NF-κB in bursa of Fabricius, spleen and thymus, which suggested that IRF-1 and NF-κB could regulate the expression of RIG-1.It was the first report about the promoter sequence of duck RIG-1. The findings in characteristics of duck RIG-1 promoter region, and the relationships between RIG-1 and its transcription factors reflected by mRNA expression profiles in immune organs of embryonic stages may provide a basis and direction to explore transcriptional regulation and expression of duck RIG-1.